DPD (REGIONAL REPRESENTATIVE COUNCIL), AS A STATE AGENCY OF INDONESIAN STATE SYSTEM, RUNS THE AUTHORITY OF ITS ROLE AND FUNCTION TO CREATE THE EXISTENCE OF BICAMERAL SYSTEM IN INDONESIA - John Paulus Pile Tukan; Lita Tyesta ALW (Diponegoro Law Review, 2018)
DPD (Regional Representatives Council) which is the representative of the region can be a counterweight in strengthening the parliamentary system in Indonesia. Since the amendment begun, the Indonesian parliamentary system has changed from a unicameral system to a bicameral system. However, if noticed, the functions, powers and duties set forth in Article 22 D of the 1945 Constitution and Law No.22 of 2003 on the composition and position of MPR (People’s Consultative Assembly), DPR (House of Representatives), DPD (Regional Representatives Council) and DPRD (Regional People’s Representatives Council), there are many assumptions that whether the function of Regional Representative Council can represent regional’s interests. DPD does not only serve as a counselor of regional autonomy board, and does not serve the legislature, as a country that embraces bicameral system. Bicameral is a term of representation system consisting of two chambers, which in Indonesia are known as DPR RI (House of Representatives of the Republic of Indonesia) and DPD RI (Regional Representatives Council of the Republic of Indonesia) which aims to achieve good government and the achievement of checks and balances between institutions, particularly in the legislature, which is one of the most important elements in the constitutional of the State.